HbA1c as a shared treatment goal in type 2 diabetes?: a secondary analysis of the DEBATE trial - Santos, Sara F. C.; Pentzek, Michael; Altiner, Attila; Daubmann, Anne; Drewelow, Eva; Helbig, Christian; Löffler, Christin; Löscher, Susanne; Wegscheider, Karl; Abholz, Heinz-Harald; Wilm, Stefan; Wollny, Anja (BMC primary care, 2023)
Background: Type 2 diabetes mellitus (T2DM) is a major health problem in the western world. Despite a widespread implementation of integrated care programs there are still patients with poorly controlled T2DM. Shared goal setting within the process of Shared Decision Making (SDM) may increase patient’s compliance and adherence to treatment regimen. In our secondary analysis of the cluster-randomized controlled DEBATE trial, we investigated if patients with shared vs. non-shared HbA1c treatment goal, achieve their glycemic goals. Methods: In a German primary care setting, we collected data before intervention at baseline, 6, 12 and 24 months. Patients with T2DM with an HbA1c ≥ 8.0% (64 mmol/mol) at the time of recruitment and complete data at baseline and after 24 months were eligible for the presented analyses. Using a generalized estimating equation analysis, we analysed the association between the achievement of HbA1c goals at 24 months based on their shared vs. non-shared status, age, sex, education, partner status, controlled for baseline HbA1c and insulin therapy. Results: From N = 833 recruited patients at baseline, n = 547 (65.7%) from 105 General Practitioners (GPs) were analysed. 53.4% patients were male, 33.1% without a partner, 64.4% had a low educational level, mean age was 64.6 (SD 10.6), 60.7% took insulin at baseline, mean baseline HbA1c was 9.1 (SD 1.0). For 287 patients (52.5%), the GPs reported to use HbA1c as a shared goal, for 260 patients (47.5%) as a non-shared goal. 235 patients (43.0%) reached the HbA1c goal after two years, 312 patients (57.0%) missed it. Multivariable analysis shows that shared vs. non-shared HbA1c goal setting, age, sex, and education are not associated with the achievement of the HbA1c goal. However, patients living without a partner show a higher risk of missing the goal (p = .003; OR 1.89; 95% CI 1.25–2.86). Conclusions: Shared goal setting with T2DM patients targeting on HbA1c-levels had no significant impact on goal achievement. It may be assumed, that shared goal setting on patient-related clinical outcomes within the process of SDM has not been fully captured yet.